Pengembangan budaya masak abereng dalam peningkatan status gizi balita stunting di Desa Glagahwero, Kecamatan Panti, Kabupaten Jember dengan pendekatan agronursing - Hanny Rasni; Tantut Susanto; Kholid Rosyidi Muhammad Nur; Novi Anoegrajekti (Journal of Community Empowerment for Health, 2019)
Indonesian society is an agrarian society with close family relationship. Agrarian society generally helps each other together, which is known as “abereng” in Madura. The purpose of this community empowerment study is to make the “abereng” cooking activities as the villager’s potency for improving the nutritional status of stunting children in Glagahwero Village with agronursing approach. The activities took place from 4 October to 14 December 2018 which was attended by 60 participants (40 mothers and their under-five children, 15 health cadres who mobilize “posyandu”, and 5 village officials). An agronursing approach was used to identify local food resources that could be processed into foods with high nutritional value. The activities consisted of socialization, training, establishment of cooking activists groups, handover of cooking utensils and food containers, cooking activities along with continued eating with under-five children with previously measured nutritional status. The activities held in every week each month. Among 40 under-five children, only 20 of under-five children were actively participated in “abereng” cooking four times each month. Before intervention program, under-five children who participated in this activity experienced nutritional deficiencies ranged from 1000 to 6000 gs, based on age and sex (according to WHO NCHS standards). The menus were developed from local food resources which containing high level of protein, vitamins, and minerals. After “abereng” cooking was carried out four times each month, there was increasing of weight by 200-1000 gs. People and families were able to explore potentcy, process, and serve local foods as nutritious foods for toddlers. “Abereng” cooking activity is a potential community and family activity in the village for improving the nutritional status of stunting children with agronursing approach. Community independence in improving nutritional status of children requires continous follow-up from health workers and academics for resolving the problem of malnutrition in children.